SUSCEPTIBILITY STATUS OF AEDES AEGYPTI (DIPTERA : CULICIDAE) TOWARD ORGANOPHOSPHATE INSEKTICIDES IN KUPANG CITY OF EAST NUSA TENGGARA PROVINCE - TIURMASARI E. SARAGIH; MARIA ERIKA RESI; BYANTARSIH WIDYANINGRUM (JURNAL INFO KESEHATAN, 2015)
Background: Organophosphate insecticides had been used in Kupang City of East Nusa Tenggara Province far before Kupang City was established in 1996. Determination of susceptibility status toward organophosphate insecticides i.e. temephos and malathion in Kupang City have never been conducted. This research purpose is to know Ae. aegypti larva susceptibility status from several villages in Kupang City of East Nusa Tenggara Province toward organophosphate insecticides, particularly temephos and malathion with the biological and biochemical test. Research Method: This is pure experimental research with The Posttest-Only Control Group Design for biological test and non-experimental tests with descriptive and analytical designs for the biochemical test. Material and method of a biological test are referred to test regulation by WHO (1996), whereas biochemical test is referred to Lee’s method (1991). Result: a Biological test using diagnostic dosage reveals that Ae. aegypti larva from several villages being tested has resistant (RR) status toward temephos with an average larva mortality rate of <80% and susceptible (SS) status toward malathion with an average larva mortality rate of >99%. The result of qualitative and quantitative biochemical test shows that 3 villages have tolerant (SR) status with an average score of 2,0-2,5; 5 villages susceptible (SS) status with an average score of <2. The result of the quantitative biochemical test shows that 8 villages have susceptible (SS) status with AV value of <0,700, 5 villages have tolerant (SR) status with AV value of 0,700-0,900 and 2 villages have resistant (RR) status with AV value of >0,900. The statistic analysis with Oneway ANOVA significant 5% rejects the null hypothesis (H0) which means that there has been a status decrease of Ae. aegypti mosquito larva susceptibility to organophosphate insecticides. Conclusion: Temephos insecticide is not relevant anymore to be used, and it is still relevant to use malathion in the Ae. aegypti mosquito control program in several villages in Kupang City of East Nusa Tenggara Province. Research result proves that susceptibility status decrease of tested mosquito larva in a biochemical test is known to be not caused by increasing activity nonspecific of esterase and acetylcholinesterase insensitivity, but may be caused by other the factors that have not been known.